The role of biology in the development of creative abilities of students. (Experimental biology, 2016)
This article deals with the development of creative abilities of students in teaching biology at school. Using a variety of innovative learning technologies biology teacher should pay special attention to the development of creative abilities provided educational material , as well as the ability to apply in practice .In addition , the teacher should pay special attention to the educational value of learning. Since the main didactic principles when it -training and education - a single process.The study used methods of training such as equations of the method , learning to perform creative tasks , job training literature , problematic search , independent search for information through the Internet, as well as through the library.According to the results of psycho - pedagogical research , we found that the level of job allows students to explore the learning material deep , versatile, and independently analyze draw conclusions. Of the 25 students , 80% of the assigned tasks corrected easily, naturally , and 10 % of students were not able to give the right answers, 5 % of the students are not able to respond to the job. We also consider , in order to develop the self-development of educational materials necessary to conduct lessons gradually complicating the task level .
Keywords: technology; creative ability; psycho – pedagogical; innovation.